Accuracy of elastic fusion biopsy: Comparing prostate cancer detection between targeted and systematic biopsy. Issue 2 (19th October 2022) - Oderda, Marco; Albisinni, Simone; Benamran, Daniel; Calleris, Giorgio; Ciccariello, Mauro; Dematteis, Alessandro; Diamand, Romain; Descotes, Jean‐Luc; Fiard, Gaelle; Forte, Valerio; Giacobbe, Alessandro; Marquis, Alessandro; et al.
Abstract: Introduction: When performing targeted biopsy (TBx), the need to add systematic biopsies (SBx) is often debated. Aim of the study is to evaluate the added value of SBx in addition to TBx in terms of prostate cancer (PCa) detection rates (CDR), and to test the concordance between multiparametric magnetic resonance imaging (mpMRI) findings and fusion biopsy results in terms of cancer location. Methods: We performed a retrospective, multicentric study that gathered data on 1992 consecutive patients who underwent elastic fusion biopsy between 2011 and 2020. A standardized approach was used, with TBx (2–4 cores per target) followed by SBx (12–14 cores). We assessed CDR of TBx, of SBx, and TBx+SBx for all cancers and clinically significant PCa (csPCa), defined as ISUP score ≥2. CDR was evaluated according to radiological and clinical parameters, with a particular focus on PI‐RADS 3 lesions. In a subgroup of 1254 patients we tested the discordance between mpMRI findings and fusion biopsy results in terms of cancer location. Uni‐ and multivariable logistic regression analyses were performed to identify predictors of CDR. Results: CDR of TBx+SBx was 63.0% for all cancers and 38.8% of csPCa. Per‐patient analysis showed that SBx in addition to TBx improved CDR by 4.5% for all cancers and 3.4% for csPCa. Patients with lesions scored as PI‐RADS 3, 4, and 5 were diagnosed with PCa in 27.9%, 72.8%, and 92.3%, and csPCa in 10.7%, 43.6%, and 69.3%, respectively. When positive, PI‐RADS 3 lesions were ISUP grade 1 in 61.1% of cases. Per‐lesion analysis showed that discordance between mpMRI and biopsy was found in 56.6% of cases, with 710 patients having positive SBx outside mpMRI targets, of which 414 (58.0%) were clinically significant. PSA density ≥0.15 was a strong predictor of CDR. Conclusions: The addition of systematic mapping to TBx contributes to a minority of per‐patient diagnoses but detects a high number of PCa foci outside mpMRI targets, increasing biopsy accuracy for the assessment of cancer burden within the prostate. High PSA‐density significantly increases the risk of PCa, both in the whole cohort and in PI‐RADS 3 cases.